2019
DOI: 10.21608/zvjz.2019.4212.1001
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Effects of the Double Immunization with Formalized Killed Vaccine against Pasteurella multocida Challenge in Rabbits

Abstract: The disease caused by Pasteurella multocida is an extremely common and difficult issue of rabbits utilized for biomedical research. The vaccination techniques are dependably the most powerful preventive measures. In the present study, 30 New Zealand rabbits (1.5 kg average body weight and 6-8 weeks old) were divided into 3 groups, control group (I), challenged nonvaccinated group (II), and challenged double vaccinated group (III). 1 st dose was administered at the 1 st day followed by similar booster dose afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
2
3
0
Order By: Relevance
“…Alveolar collapse, tissue destruction and compensatory emphysema. Our results were in agreement with (Mohamed et al, 2019) who proved that lung of Pasteurella infected rabbit revealed extensive hemorrhage with presence of large numbers of extravasated RBCs in the alveolar lumens. (Alam et al, 2018) observed that the lung tissue of normal control rabbits exhibited normal bronchial and bronchiolar structures with normal alveolar and perialveolar capillaries.…”
Section: Histopathological Changessupporting
confidence: 93%
See 4 more Smart Citations
“…Alveolar collapse, tissue destruction and compensatory emphysema. Our results were in agreement with (Mohamed et al, 2019) who proved that lung of Pasteurella infected rabbit revealed extensive hemorrhage with presence of large numbers of extravasated RBCs in the alveolar lumens. (Alam et al, 2018) observed that the lung tissue of normal control rabbits exhibited normal bronchial and bronchiolar structures with normal alveolar and perialveolar capillaries.…”
Section: Histopathological Changessupporting
confidence: 93%
“…On the other hand, spleen of infected non treated group showed severe congestion and focal depletion of white pulp. our study was in agreement of (Mohamed et al, 2019) who observed severe lymphoid depletion of the lymphoid follicle associated with hemosiderosis. Spleen showed necrosis, edema and lymphoid depletion of lymphoid follicles of the white pulp (El-Demerdash et al, 2015).…”
supporting
confidence: 93%
See 3 more Smart Citations